1999
DOI: 10.1084/jem.190.4.497
|View full text |Cite
|
Sign up to set email alerts
|

Novel Point Mutation in the Extracellular Domain of the Granulocyte Colony-Stimulating Factor (G-Csf) Receptor in a Case of Severe Congenital Neutropenia Hyporesponsive to G-Csf Treatment

Abstract: Severe congenital neutropenia (SCN) is a heterogeneous condition characterized by a drastic reduction in circulating neutrophils and a maturation arrest of myeloid progenitor cells in the bone marrow. Usually this condition can be successfully treated with granulocyte colony-stimulating factor (G-CSF). Here we describe the identification of a novel point mutation in the extracellular domain of the G-CSF receptor (G-CSF-R) in an SCN patient who failed to respond to G-CSF treatment. When this mutant G-CSF-R was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
3
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 60 publications
1
82
3
1
Order By: Relevance
“…Homozygous deletion of G-CSFR or G-CSF causes severe neutropenia in mice, 21,22 and heterozygous mutations of G-CSFR have been linked to sporadic cases of severe congenital neutropenia. 23 As both Gfi1 transcriptional regulation and G-CSF/ G-CSFR signaling are critical to neutrophil maturation, we have investigated whether their activities might be linked. We find that Gfi1 functions as a regulator of G-CSF/G-CSFR signaling in myeloid cells by promoting expression of RasGRP1 (Ras guanine nucleotide releasing protein 1), which is shown to be a critical modulator of G-CSF/G-CSFR-induced Ras activation.…”
Section: Introductionmentioning
confidence: 99%
“…Homozygous deletion of G-CSFR or G-CSF causes severe neutropenia in mice, 21,22 and heterozygous mutations of G-CSFR have been linked to sporadic cases of severe congenital neutropenia. 23 As both Gfi1 transcriptional regulation and G-CSF/ G-CSFR signaling are critical to neutrophil maturation, we have investigated whether their activities might be linked. We find that Gfi1 functions as a regulator of G-CSF/G-CSFR signaling in myeloid cells by promoting expression of RasGRP1 (Ras guanine nucleotide releasing protein 1), which is shown to be a critical modulator of G-CSF/G-CSFR-induced Ras activation.…”
Section: Introductionmentioning
confidence: 99%
“…Whether this mechanism could be responsible for increased responsiveness to growth factors observed in hematological disorders such as polycythemia vera remains to be determined. Interestingly, it has been recently shown that mutations in the G-CSF receptor that inhibit ligand-induced internalization and lead to extended receptor activation frequently occurred in acute myeloid leukemia (47,48),…”
Section: -The Internalized Receptors Are Not Tyrosine Phosphorylatedmentioning
confidence: 99%
“…15,16 Rarely, somatic or de novo heterozygous CSF3R mutations in the extracellular region of the G-CSFR have been described. [17][18][19][20] These mutants are characterized by hyporesponsiveness to rhG-CSF and act in a dominant-negative fashion by interfering with proper function of the wild-type (WT) G-CSFR. Additionally, a heterozygous germline CSF3R mutation has been associated with neutrophilia.…”
Section: Introductionmentioning
confidence: 99%